Hylin a1, the first cytolytic peptide isolated from the arboreal South American frog Hypsiboas albopunctatus ('spotted treefrog') - Castro, Mariana S.; Ferreira, Tania Cristina G.; Cilli, Eduardo Maffud [UNESP]; Crusca, Edson [UNESP]; Mendes Giannini, Maria José Soares [UNESP]; Sebben, Antonio; Ricart, Carlos Andre; Sousa, Marcelo V.; Fontes, Wagner (Elsevier B.V., 2009)
RP-HPLC fractionation of the electrically stimulated skin secretion of the arboreal South American frog Hypsiboas albopunctaturs (spotted treefrog) led to the isolation of a cytolytic C-terminally amidated peptide. This novel peptide, named hylin a1 (Hy-a1), consists of 18 amino acid residues (IFGAILPLALGALKNLIK-NH(2)). The alpha-helical structure of the synthetic hylin a1 peptide was confirmed by CID spectroscopy in the presence of 60% (v/v) TFE. The synthetic peptide displayed broad-spectrum antimicrobial activity against Gram-negative and Gram-positive bacteria including Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Bacillus subtilis and Pseudomonas aeruginosa and also against fungi (Candida albicans, C. krusei, C. parapsilosis and Cryptococcus neoformans). Hylin a1 was also able to disrupt human erytrocytes (HC(50) = 18 mu M). Similarity analysis using PSI-BLAST revealed 50-44% of identity to maximins Hv, H16, H15 and H10 from Bombina maxima and also to hylins b1 and b2 (Hy-b1 and Hy-b2) from Hypsiboas lundii (synonym: Hyla biobeba). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Amphibian; Hypsiboas; Skin secretion; Hemolysis; Antimicrobial peptide